THE EFFECT OF SERVICE QUALITY ON SUSTAINABLE COMPETITIVE ADVANTAGE. MARKETING CAPABILITIES ARE AN INTERACTIVE VARIABLE -A SURVEY STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS AND VISITORS AT AL-MOWASAT PRIVATE HOSPITAL IN BASRAH - Prof. Dr. Hashim Nayef Hashim Al-Hachim (Scholars Digest Publishing, 2024)
The study aims to reveal the relationship between service quality as an independent variable and marketing capabilities as an interactive variable to achieve a sustainable competitive advantage at a good level as a dependent variable. The problem of this study was embodied in a main question: What is the effect of improving service quality on sustainable competitive advantage through marketing capabilities as an interactive variable? The importance of the study stems from its focus on an important sector in the world today, which is the services sector in general and the health services sector in particular because of its importance in supporting the humanitarian aspect and supporting the economic activity of the country. The descriptive analytical method was used to conduct the analysis process to determine the influence relationships and correlation between the special variables. Through the study, the study reached a set of conclusions, the most prominent of which is that senior management’s support for employees is an essential pillar for building a sustainable competitive advantage through its support and assistance to individuals working in the hospital and providing specialized training programs to raise the level of services provided through distinguished skills and capabilities, in addition to raising their awareness to raise levels of service. Higher to ensure continuity and survival in light of intense competition, in addition to the importance of focusing on marketing capabilities.
Keywords: service quality, marketing capabilities, sustainable competitive advantage.